Giovan Battista Oddoni fra idillio, lirica, tragedia e pastorale - Giuseppe Alonzo (Annali Online dell'Università di Ferrara. Sezione Lettere)
Through archival sources and repertories this paper offers a biographical and bibliographical outline of Giovan Battista Oddoni, born in Varese and employed in Milan, Mantua and Turin from 1618 to 1630. The paper enlightens in particular on his academic and courtesan relations, especially with the Houses of Gonzaga and Visconti Borromeo from Lainate, then, after a forced transfer in Turin due to legal problems, with the House of Savoy. The paper also discusses the history of composition, structures and contents of Idillii (1618), the tragedy Edemondo (1621) and Rime (1623), published in Milan; of them, the paper shows the aspects encoded in the respective genres (with a raid on the history of seventeenth century’s idyll in Lombardy). Finally, the paper discusses the tragicomedy Arione (1628), published and performed in Turin, which is ascribed for the first time to the author (previously limited to the symbol «G.B.O.» that appears in the frontispiece). The paper considers this ‘maritime fable’ for its courtesan, allegorical and didactic purposes, as well as for the reuse of expressive formulas and plot schemas taken from Oddoni’s previous literary experience.